Accidental Explosions, Beirut ANFO Blast, Ghana Truck Explosion, Global Terrorism Index 2021-22, and Blast Mitigation: A Review - Anas S.M.; Al-Dala'ien R.N.; Akram S.; Alam M. (EDP Sciences, 2025)
Explosions are continually occurring without ceasing in many parts of the world endangering human lives and seriously affecting the health of infrastructures and facilities. Industry accidental mishaps that occurred recently, like those in Ghana (2022; 17 deaths), Russia (2021; 18 deaths), Beirut (2020; 220 deaths; $8bn economic loss), and Tientsin (2015, 173 deaths; $6.86bn economic loss), indicate the severity of the industrial devastation one could gauge that explosions may cause. Very recently, another industrial blast occurred at a rocket and explosive factory in the capital city of Turkey leading to the collapse of a nearby building and causing 5 deaths and serious injuries to over 50 civilians, is an eye-opener. This article offers a condensed examination of subjects related to explosions, including accidental detonations, the Beirut ANFO explosion, and the Ghana truck explosion. The report findings from the global terrorism index 2021-22 are analyzed and discussed. Additionally, strategies for both active and passive measures to mitigate the impact of explosions on infrastructure and facilities are emphasized. To ensure safety and durability against damage, the structure needs to possess resilience in the face of explosions. Therefore, it is crucial to analyze how the structure responds to extreme loading in order to enhance the design philosophy. Currently, there is still a lack of understanding regarding the mechanism of blast and how it affects masonry structures. Consequently, further research is required to delve deeper into this subject. ? 2024 EDP Sciences. All rights reserved.